2007
DOI: 10.1016/j.rmed.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year time course of lung function, symptoms, health-related quality of life, and exercise tolerance in COPD patients undergoing pulmonary rehabilitation programs

Abstract: Despite progressive lost in effectiveness of repeated PRP, COPD patients undergoing those programs do not show any significant worsening in exercise tolerance, dyspnoea and HRQL along a period of 7 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 39 publications
9
84
3
5
Order By: Relevance
“…These findings are in accordance with the above-mentioned studies by Dourado et al, 37 Foglio et al, 39 and Normandin et al 40 with no differences between groups.…”
Section: Effect Of Aerobic Training Intensity On Symptom Controlsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in accordance with the above-mentioned studies by Dourado et al, 37 Foglio et al, 39 and Normandin et al 40 with no differences between groups.…”
Section: Effect Of Aerobic Training Intensity On Symptom Controlsupporting
confidence: 93%
“…There is evidence of a positive effect on HRQOL, as shown by studies by Bernard et al, 34 Pereira et al, 35 Montes de Oca et al, 36 Dourado et al, 37 Arnardóttir et al, 38 and Foglio et al, 39 , even considering the wide range of intensities in those heterogeneous pulmonary rehabilitation program interventions (type, modality, duration, and frequency). The multi-center study by Laviolette et al 28 with 168 subjects with COPD also found improvement in the SGRQ after the pulmonary rehabilitation program but lacked any description of the exercise intensity applied.…”
Section: Effect Of Aerobic Training Intensity On Hrqolmentioning
confidence: 93%
“…Assessing exercise capacity in an interview is difficult and prone to error, but the self-reported measure 'flights of stairs' was previously considered as reliable [Reilly et al 1999]. In many patients with COPD, the impaired exercise capacity is directly related to their quality of life [Foglio et al 2007;Dowson et al 2001]. …”
Section: Discussionmentioning
confidence: 99%
“…In severe COPD, there is a close association between changes in a systemic and multidimensional index of performance and functional status (body mass index, airflow obstruction, dyspnoea and exercise capacity index) induced by PR and patient outcomes [22]. Several strategies have been suggested to maintain these benefits in the long term [23].…”
Section: Rehabilitationmentioning
confidence: 99%